2009
DOI: 10.1002/bit.22405
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mammalian cell death by simple shear and extensional flows

Abstract: In this work we investigated whether the type of shear flow, to which cells are exposed, influences the initiation of cell death. It is shown that mammalian cells, indeed, distinguish between discrete types of flow and respond differently. Two flow devices were employed to impose accurate hydrodynamic flow fields: uniform steady simple shear flow and oscillating extensional flow. To distinguish between necrotic and apoptotic cell death, fluorescence activated cell sorting and the release of DNA in the culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 47 publications
4
60
0
Order By: Relevance
“…Previous experiments have shown that cells undergo significant stretching and deformation in extensional flows, leading to cell death. 37,38 Further, extensional flow is commonly used to stretch and fragment DNA for high throughput sequencing. 39,40 HUVEC in a saline carrier subjected to syringe needle flow (which includes extensional and linear shear flows) resulted in 58.7% viability (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that cells undergo significant stretching and deformation in extensional flows, leading to cell death. 37,38 Further, extensional flow is commonly used to stretch and fragment DNA for high throughput sequencing. 39,40 HUVEC in a saline carrier subjected to syringe needle flow (which includes extensional and linear shear flows) resulted in 58.7% viability (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The maximal shear stress value in a 1-L OSR agitated at 110 rpm with a working volume of 300 mL was one to two orders of magnitude lower than values reported to be harmful for CHO cells [2]. This indicates that standard cultivation conditions in OSRs are safe for sensitive mammalian cells.…”
Section: Discussionmentioning
confidence: 95%
“…Mammalian cells exhibit different thresholds for shear versus tensile-stress-induced death, initiating apoptosis when they are exposed to approximately 2 Pascals of oscillatory extensional stress [12]. The following stress thresholds initiate undesirable necrotic death; 1 Pascal of steady shear versus 500 Pascals of oscillatory extension [12]. Both types of death mechanisms have been described empirically by the 1st-order rate expression in Eq.…”
Section: Verification Of Creeping-flow On the Length-scale Of An Isolmentioning
confidence: 98%
“…When vortex formation and bubble entrainment are absent in agitated gas-liquid reactors, Kunas and Papoutsakis [23] demonstrate that suspended hybridoma cells are damaged at impeller speeds above 700 rpm via bulk turbulent stress. Mammalian cells exhibit different thresholds for shear versus tensile-stress-induced death, initiating apoptosis when they are exposed to approximately 2 Pascals of oscillatory extensional stress [12]. The following stress thresholds initiate undesirable necrotic death; 1 Pascal of steady shear versus 500 Pascals of oscillatory extension [12].…”
Section: Verification Of Creeping-flow On the Length-scale Of An Isolmentioning
confidence: 99%
See 1 more Smart Citation